Sustained Tumor Control With MAPK Inhibition in BRAF V600–Mutant Adult Glial and Glioneuronal Tumors. (17th August 2021) - Berzero, Giulia; Bellu, Luisa; Baldini, Capucine; Ducray, François; Guyon, David; Eoli, Marica; Silvani, Antonio; Dehais, Caroline; Idbaih, Ahmed; Younan, Nadia; Nguyen-Them, Ludovic; Gaillard, Stephan; et al.
Abstract : Objective: To assess whether RAF and MEK inhibitors (RAFi/MEKi) can provide long-term clinical benefit in adult patients with BRAF V600–mutant glial and glioneuronal tumors (GGNTs), we analyzed tumor response and long-term outcome in a retrospective cohort. Methods: We performed a retrospective search in the institutional databases of 6 neuro-oncology departments for adult patients with recurrent or disseminated BRAF V600–mutant GGNTs treated with RAFi/MEKi. Results: Twenty-eight adults with recurrent or disseminated BRAF V600–mutant gangliogliomas (n = 9), pleomorphic xanthoastrocytomas (n = 9), and diffuse gliomas (n = 10) were included in the study. At the time that treatment with RAFi/MEKi was started, all tumors displayed radiologic features of high-grade neoplasms. Thirteen patients received RAFi as single agents (vemurafenib [n = 11], dabrafenib [n = 2]), and 15 received combinations of RAFi/MEKi (vemurafenib + cobimetinib [n = 5], dabrafenib + trametinib [n = 10]). Eleven patients achieved a partial or complete response (11 of 28, 39%), with a median reduction of −78% in their tumor burden. Responders experienced a median increase of 10 points in their Karnofsky Performance Status (KPS) score and a median progression-free survival of 18 months, which was longer than achieved with first-line treatment (i.e., 7 months, p = 0.047). Responders had better KPS score ( p = 0.018) and tended to be younger ( p = 0.061) and to be treated earlier ( p = 0.099) compared to nonresponders. Five patients were rechallenged with RAFi/MEKi at progression, with novel tumor responses in 2. On univariate and multivariate analyses, response to RAFi/MEKi was an independent predictor of overall survival. Conclusions: Our study highlights the long-term clinical benefits of RAFi/MEKi in adult patients with BRAF V600–mutant GGNTs and encourages rechallenge in responders. Classification of Evidence: This study provides Class III evidence that, for adult patients with BRAF V600-mutant GGNT, RAFi/MEKi can reduce tumor burden and provide clinical benefit.